Study of the Genotoxic Effects of Polluted Water of Certain Ponds of Narsinghpur in the R.B.Cs. of the Fish Labeo rohita by Applying Micronucleus Assay - Girdoniya, V (International Journal of Pharmaceutical & Biological Archive, 2015)
Study of the Genotoxic Effects of Polluted Water of Certain Ponds of Narsinghpur in the R.B.Cs. of the Fish Labeo rohita by Applying Micronucleus Assay